2011
DOI: 10.1021/jp201017e
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Particle Size and Structural Properties of Mesoporous Silica Nanoparticles Using the Taguchi Method

Abstract: The Taguchi method, a statistical design with an L8 orthogonal array, was adopted to optimize the synthetic conditions of mesoporous silica nanoparticles (MSNs) with respect to particle size and structural properties. The amount of the silica source (i.e., tetraethoxysilane), pH value, and reaction time were selected as significant parameters affecting the size and structural properties of the synthesized MSNs. Particle sizes ranging from 17 to 247 nm were successfully controlled by the Taguchi method, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(144 citation statements)
references
References 34 publications
4
133
1
1
Order By: Relevance
“…Recently, Chiang et al reported the control of MSNs particle sizes from 17 to 247 nm based on the Taguchi design method, by controlling the amount of TEOS, reaction time, and pH value [164]. They investigated the effect of the different parameters that influence particle size, resulting in the following sequence: pH (57%) > reaction time (29%) > amount of TEOS (13%).…”
Section: Modified Stöber Methodsmentioning
confidence: 99%
“…Recently, Chiang et al reported the control of MSNs particle sizes from 17 to 247 nm based on the Taguchi design method, by controlling the amount of TEOS, reaction time, and pH value [164]. They investigated the effect of the different parameters that influence particle size, resulting in the following sequence: pH (57%) > reaction time (29%) > amount of TEOS (13%).…”
Section: Modified Stöber Methodsmentioning
confidence: 99%
“…The synthetic process has a strong influence on the resulting MSN particles, pH in particular, allowing for fine control of particle size, etc. [34]. Additionally, alcohols with long alkyl chains have been shown to affect MSN particle size by altering the tetraalkylsilicate hydrolysis kinetics [35].…”
Section: Mesoporous Silica Nanoparticles: Ideal Candidates For Proteimentioning
confidence: 99%
“…The tremendous attentions on MSNs are due to its desirable properties such as high surface area, large pore volume and easy functionalization [2,3]. Furthermore, this material can be tailored according to the type of applications and some of the common applications of this material are as catalyst, absorbent, in separation techniques and in the biomedical industry [1,[4][5][6]. However, for biomedical applications, it is important that the MSNs generated are monodispersed with particles size < 100 nm as it is advantageous in cell endocytosis process [7].…”
Section: Introductionmentioning
confidence: 99%